INVESTIGATORS DISCOVERED A SHOOTING ACTION AGAINST A DRUG DISTRIBUTOR LINKED TO HUMAN RIGHTS PROTECTION - Herlambang, Herlambang; Bridges, Jim W. (EQUALEGUM International Law Journal, 2024)
Background. Police officers have the right to exercise their discretion whenever they decide to take action, and they occasionally abuse this authority. The purpose of this research is to examine the use of lethal force by law enforcement against drug trafficking, which is considered a violation of human rights. Research Method. The technique utilized in research is Normative Juridical, which combines an empirical and juridical perspective. Findings. One could argue that when police officers shoot drug dealers on the spot, they are violating their human rights. If the dealer is being shot on the spotThese drugs are not governed by the human rights and humanism principles of law enforcement; therefore, there will be flagrant abuses of human rights, as well as police efforts to disclose drug trafficking instances to prevent human rights violations. The police made an effort in several ways, including working with prior drug networks to help the National Police identify a drug network, maximizing resources that already exist in terms of human resources, can reducing the flow of drugs by carrying out raids, monitoring, and using disguise and undercover tactics. Conclusion. In situations where force is applied, violence is essentially used.